Concise Total Synthesis of (−)‐Affinisine Oxindole, (+)‐Isoalstonisine, (+)‐Alstofoline, (−)‐Macrogentine, (+)‐Na‐Demethylalstonisine, (−)‐Alstonoxine A, and (+)‐Alstonisine. Issue 62 (18th October 2017) - Stephen, Michael Rajesh; Rahman, M. Toufiqur; Tiruveedhula, V. V. N. Phani Babu; Fonseca, German O.; Deschamps, Jeffrey R.; Cook, James M.
Abstract: A highly enantio‐ and diastereoselective strategy to access any member of the sarpagine/macroline family of oxindole alkaloids via internal asymmetric induction was developed from readily availabled ‐(+)‐tryptophan. At the center of this approach was the diastereospecific generation of the spiro[pyrrolidine‐3, 3′‐oxindole] moiety at an early stage via a tert ‐butyl hypochlorite‐promoted oxidative rearrangement of a chiral tetrahydro‐β‐carboline derivative. This key branching point determined the spatial configuration at the C‐7 spiro center to be entirely 7 R or 7 S . Other key stereospecific processes were the asymmetric Pictet–Spengler reaction and Dieckmann cyclization, which were scalable to the 600 and 150 gram levels, respectively. Execution of this approach resulted in first enantiospecific total synthesis of (+)‐isoalstonisine and (−)‐macrogentine from the chitosenine series (7 R ), as well as (+)‐alstonisine, (+)‐alstofoline, (−)‐alstonoxine A and (+)‐ N a ‐demethylalstonisine from the alstonisine series (7 S ). Abstract : Enantioselective total synthesis : A highly enantio‐ and diastereoselective strategy to access any member of the sarpagine/macroline family of oxindole alkaloids by internal asymmetric induction was developed. The diastereospecific generation of the spiro[pyrrolidine‐3, 3′‐oxindole] moiety at an early stage from a t‐ BuOCl‐promoted oxidative rearrangement of a chiral tetrahydro‐β‐carboline derivative determined the C‐7 spiro center to be either R or S . Execution of this approach resulted in first enantiospecific total synthesis of the shown alkaloids.